Financial Technology and Digital Tax Education at Yayasan Pendidikan Pangeran Antasari - Khana Saputri; Agus Tina; Ninta Katharina; Wiliam Wiliam; Afriza Amir (Wahana Jurnal Pengabdian kepada Masyarakat, 2025)
The rapid development of financial technology (fintech) and the digitalization of tax administration have transformed financial services and public sector systems in Indonesia. These changes require young generations to develop adequate financial literacy and digital tax awareness, enabling them to use digital financial services safely and understand basic tax obligations. This community service program aims to provide education on secure fintech usage, identifying illegal financial platforms, and conducting tax payments through the Coretax application for Grade XI students at Yayasan Pendidikan Pangeran Antasari. The activities were carried out through socialization, lectures, discussions, and practical demonstrations involving 40 students. The results show a significant increase in students’ understanding of fintech benefits and risks, cybersecurity awareness, and digital tax procedures. The program also fostered early tax consciousness and appreciation of taxpayer responsibilities in the digital era. Overall, this initiative contributes to strengthening financial and digital tax literacy among future taxpayers.